Perencanaan Strategis TI Di Dinas Ketahanan Pangan Dan Pertanian Palembang Menggunakan Metode Ward & Peppard - Muhammad Akbar; Dicky Pratama (BETRIK, 2025)
The development of information technology has become a crucial element in enhancing governance efficiency and improving public service quality, particularly within the Palembang City Food Security and Agriculture Office (DKPP), which plays a strategic role in ensuring regional food stability. However, evaluation results indicate that the utilization of information systems within DKPP remains suboptimal, especially in integrating food data, digitizing operational processes, and supporting data-driven decision-making. This study aims to formulate a strategic Information Systems and Information Technology (IS/IT) plan aligned with organizational needs using the Ward and Peppard framework. Data collection was conducted through observation, interviews, and document analysis. The assessment of internal conditions was carried out using the Value Chain model, while external factors were examined through PESTEL analysis. The findings were then synthesized using SWOT analysis and Critical Success Factor (CSF) identification to determine strategic priorities. The study recommends the development of an integrated Food and Agriculture Information System as the core platform to unify food price data, food balance sheets, smart farming initiatives, food distribution processes, and food safety monitoring. Furthermore, a future application portfolio was formulated using the McFarlan Strategic Grid, accompanied by a five-year implementation roadmap to guide progressive IS/IT development. The resulting strategic plan is expected to strengthen DKPP’s digital ecosystem, improve operational efficiency, and support more accurate and responsive decision-making in addressing regional food security challenges.